A dinâmica da atividade do turismo arqueológico na perspectiva do desenvolvimento no município de Ingá, PB - Silva, Denymagna (2019)
Archaeological heritage represents a great potential for tourism, as it has an enormous capacity to generate economic and social development. The Itacoatiara Archaeological Site, located in the geographical area of Ingá (7 ° 16 ′ S, 35 ° 36 'W), intermediate region of Campina Grande, PB, is a monument listed by the Institute of Artistic and National Heritage and has a group. of rocky panels, with dozens of rock inscriptions, with messages that are not yet deciphered. The reasons that motivated the choice of the research theme are based on the lack of studies on tourism activity in the referred Archaeological Site and the perspective of development in this territorial outline, these determinations being the main objectives. The methodological procedures were exploratory, through interviews applying a questionnaire, with questions related to social profile, public management assessment, tourist attractions, limiting factor to tourism development, among others. The interviewees were randomly selected, consisting of a universe of twenty social actors, with direct action in the tourism segment. The research data (documentary and collected) were analyzed using descriptive statistics criteria, using the Excel spreadsheet in the calculations and in the making of tables, tables and graphs. The main results indicated that the Itacoatiara Archaeological Site was the first listed archaeological monument, as a national archaeological heritage. The appreciation of the heritage of recorded inscriptions shows that this was not a common place. Handicraft is an activity that reflects local knowledge, as well as being an alternative for local development. The profile of the social actors who work in the tourism segment of Ingá, PB, has an age group of over 30 years old, elementary and high school level and income of up to two minimum wages. Tourism activity in the municipality of Ingá is basically managed by direct administration (Municipal Secretariat of Tourism) and there are also state and non-state social participation spaces formally institutionalized at the local level. There is little investment in the Itacoatiara Archaeological Site to encourage archaeological or cultural tourism, and the need for improvements in local tourism infrastructure, such as transportation, signage, lodging, tourist itineraries and recreational space on site